Problems of formation country brand of Kazakhstan at the modern stage. (Journal of Economic Research & Business Administration, 2016)
Brand country – forms the country’s image on the world stage and a positive opinion about the country of foreign nationals. Successfully created the country’s brand improves the socio-economic situation in the country and contributes directly to the development of culture, sports and tourism of the country. To date, the formation of the country brand is of particular importance for improving the competitiveness of the Republic of Kazakhstan. In this regard, this article provides problems of the formation of country brand in Kazakhstan at the modern stage. The article deals with a political brand and image, an export brand, tourism brand, brand investment, brand culture, people as a national brand of Kazakhstan. Also the article analyzed the perspectives and directions of the development of the country brand in Kazakhstan.
Keywords: brand; branding; the brand of the country; the country’s image; economy; tourism; export; policies; investment; arts; sport.